Contribution of China's online car-hailing services to its 2050 carbon target: Energy consumption assessment based on the GCAM-SE model. (January 2022) - Wu, Tian; Wang, Shouyang; Wang, Lining; Tang, Xiao
Abstract: As online car-hailing services in China have matured and gained legitimacy as a traffic business activity supported by national policies, they have exceeded the expected speed of development. This paper estimates the extent to which online car-hailing services will affect China's energy consumption and carbon emissions under several scenarios. To weigh the substitution effect of online car hailing toward China's 2050 environmental goals, a Global Change Assessment Model 4.0-Sharing Economic (GCAM-SE) is used to analyze and associated government policy. Results indicate that by 2050 China's online car-hailing will achieve emission reductions of 8.36, 14.51, and 95.66 MTCO2 under, respectively, strict, moderate, and non-strict levels of the national Preliminary Rules on the Management of Online Car Hailing (PRMOCH). In 2015–2033, strict PRMOCH can better reduce energy consumption and carbon emissions by controlling the number of online car-hailing services, as compared to non-strict PRMOCH. After 2033, online car-hailing services will automatically realize the emission reduction function, whereas in this study's scenarios 1 and 2, the PRMOCH will hinder realizing car hailing's intended emission reduction function. These results strongly suggest the policy for online car hailing will be counterproductive unless policy makers consider the difference between the PRMOCH validity period and invalidity period. Highlights: Consider the substitution effect of online car hailing, proposing the GCAM-SE model. Estimate extent to which online car-hailing will affect China's energy consumption. Analysis requirements of Preliminary Rules on the Management of Online Car Hailing. Contribution of China's online car-hailing services to its 2050 carbon target.